PENGETAHUAN DAN UPAYA KONSERVASI KAYU SOWANG (Xanthostemon sp.) MASYARAKAT KAMPUNG DOYO LAMA DAN KAMPUNG HARAPAN PADA KAWASAN CAGAR ALAM PEGUNUNGAN CYCLOOP - AISOI, LEONARDO ELISA (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2021)
This research was conducted to determine the knowledge and conservation efforts of the people of Doyo Lama villageand Harapanvillage. The research was carried out for three months, namely, from July to September 2020, using the observation method; interview method; documentation method; and literature study methods, and analyzed descriptively qualitatively. The results showed that knowledge about sowang wood (Xanthostemon sp.), is a traditional knowledge passed down from generation to generation orally. The people of Doyo Lama village call sowang by the name toang (meaning hard and strong), and Harapan village named howan(meaning wood that is durable and not easily weathered). The people of Doyo Lamavillage know two species of sowang wood, namely broad-leaved species and small-leaved species. The people ofHarapan villagealso recognize two species, namely the red-flowered species and the yellow-flowered species. The broad-leaved species and the red-flowered species are Xanthostemonnovoguineensis species. While the species with small leaves and yellow flowers are Xanthostemonpapuanus. Traditional knowledge and use of sowang wood by the people of Doyo Lama villageand Harapanvillage is decreasing, influenced by the development of modern life, because until now there have been no efforts and conservation activities for sowang wood in the two villages and there has been a shift in cultural values from traditional be modern. While the species with small leaves and yellow flowers are Xanthostemonpapuanus. Traditional knowledge and use of sowang wood by the people of Doyo Lama villageand Harapanvillage is decreasing, influenced by the development of modern life, because until now there have been no efforts and conservation activities for sowang wood in the two villages and there has been a shift in cultural values from traditional be modern. While the species with small leaves and yellow flowers are Xanthostemonpapuanus. Traditional knowledge and use of sowang wood by the people of Doyo Lama villageand Harapan villageis decreasing, influenced by the development of modern life, because until now there have been no efforts and conservation activities for sowang wood in the two villages and there has been a shift in cultural values from traditional be modern